ARTISTIC AND LEGAL MECHANISMS OF ADDRESSING SOCIAL PROBLEMS IN THE WORKS OF GAFUR GULAM - Ramazonova , Sevinch (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This article analyzes social problems reflected in the works of Gafur Ghulam and examines the role of law in addressing them through an artistic-legal approach. Issues such as poverty, social inequality, bureaucratic indifference, and educational problems are presented as systemic phenomena in the writer’s works. The study highlights the importance of legal protection and preventive mechanisms in ensuring social balance.